The usefulness of wide excision assisted by a computer navigation system and reconstruction using a frozen bone autograft for malignant acetabular bone tumors: a report of two cases - Abe, Kensaku (BMC Cancer, 2018)
BACKGROUND: Difficult resection of tumors from regions with complex local anatomy, such as the pelvis and sacrum, is likely to result in inadequate surgical margins (intralesional or marginal); this is because three-dimensional osteotomy is difficult particularly around the acetabulum. Additionally, removal of the joint makes reconstruction very difficult; thus, retention of good function also becomes difficult. In musculoskeletal oncology, computer navigation systems are still not widely used to prevent tumor-positive margins. We performed wide excision with guidance from a computer navigation system and reconstruction using frozen bone autografts for malignant pelvic bone tumors in two patients, and we obtained excellent functional and oncological outcomes. Here we present these patients and discuss our approach. CASE PRESENTATION: Case 1: A 12-year-old girl presented with Ewing sarcoma of the left pelvis (PI-II). We performed wide excision assisted by a computer navigation system with the osteotomy of the load surface of acetabulum and reconstruction using a frozen bone autograft. At the final follow-up, she showed excellent function and was alive without the disease. Moreover, she did not have osteoarthritis of the left hip joint. Case 2: A 71-year-old woman presented with dedifferentiated chondrosarcoma of the right pelvis (PII-III). We performed wide excision assisted by a computer navigation system with osteotomy avoiding load surface of the acetabulum and reconstruction using a frozen bone autograft; there was no tumor at the load surface. At the final follow-up, she showed good function, was alive without the disease, and did not have osteoarthritis of the left hip joint. CONCLUSIONS: Wide excision assisted by a computer navigation system and reconstruction using a frozen bone autograft are very useful for the management/treatment of extremely difficult cases such as malignant pelvic bone tumors, particularly those including the acetabulum.